Social media impact on trading behavior: An examination among Indonesian young adult investors with capital market literacy as a mediator - Junaidi, Junaidi; Nurhidayah, Nurhidayah (University of Islam Malang, 2023)
The decline in financial literacy about capital markets among Indonesians raises concerns that the growing number of investors is at risk of financial fraud. This study introduces a novel approach to comprehensively examine how Indonesian young adults make investment choices, mainly when influenced by social media and their different literacy levels about financial markets in the digital age context. The central and dual roles of capital market literacy as an independent and intervening variable expand upon the existing framework of related studies. An empirical online survey with a valid sample of 314 respondents from Indonesia is used as the primary data for the study. Using the partial structural equation model, our results indicate that both social media and capital market literacy directly and positively impact investors' trading behavior. This suggests that a deeper understanding of capital market literacy, coupled with the influence of social media, plays a crucial role in shaping how investors engage in trading activities. Furthermore, this study also found that the mediating role of capital market literacy significantly affects trading behavior, indicating its importance in explaining how social media influences investment decisions among young adults.